Pelatihan Pembuatan Sabun Herbal Berbahan Serai (Cymbopogon ciratus) Sebagai Pengembangan Keterampilan Warga Belajar di PKBM Al Manar Medan - Brema Pardamean Gultom; Efata Sianturi; Elena Agnesia Tambunan; Geovani Adelina Sitepu; Hangelika.O. Butar-butar; Hasana Gurium; Heflindo Sinanga; Paskah Aritonang Simare-mare; Rentaida Fellyesa Munthe; Ribka Eirene Zai; Rifa Wahyuni; Fauzi Kurniawan; Tegar Anggi Handika (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This research is motivated by the suboptimal utilization of local resources, particularly lemongrass plants, as well as the limited life skills-based empowerment program at PKBM Al Manar Medan. This study aims to analyze the use of lemongrass plants as an ingredient in making herbal soap in developing students' life skills. The study used a qualitative descriptive approach with a field research type. The research subjects consisted of 10 informants including students, tutors, and PKBM managers who were selected based on their active involvement in training activities. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis used the stages of data reduction, data presentation, and drawing conclusions. The results showed that training in making lemongrass-based herbal soap was able to improve students' practical skills, creativity, and participation in learning activities. In addition, the resulting product has economic value and has the potential to be developed as a local resource-based business. The implications of this study indicate that local potential-based training can be a community empowerment strategy that supports strengthening life skills, economic independence, and the development of more contextual and sustainable non-formal education programs